Caveolin-1 regulates OMV-induced macrophage pro-inflammatory activation and multiple Toll-like receptors - Sivanantham, Ayyanar; Alktaish, Ward; Murugeasan, Selvakumar; Gong, Bin; Lee, Heedoo; Jin, Yang (Frontiers in Immunology, 2023)
Macrophages (Mϕ), the primary cell of the innate immune system, serves as the first line of defense. During bacterial infection, Gram-negative (G-) bacteria release nanosized outer membrane vesicles (OMVs), facilitating the crosstalk between the microbe and the host. The underlying mechanisms by which OMVs induced pro-inflammatory (M1) activation are still unknown. Our study shows that OMVs caused M1 activation via modulating various toll-like receptor (TLR) expressions as they contain LPS, LTA, bacterial DNAs, and flagellins. Also, we found that caveolin-1 (cav-1), a 21-kDa scaffolding protein of caveolae and lipid rafts, plays a significant role in OMV-induced pro-inflammatory response in regulating various TLR signaling pathways. Specifically, cav-1 deletion increased the expression of OMV-induced TLRs, pro-inflammatory cytokine secretions (TNF-α and IL-1β), and the reactive oxygen species (ROS) production in Mϕs. Further, we examined the interaction between Cav-1 and TLR4 by immunoprecipitation, colocalization, and computational models, providing future direction to explore the role of cav-1 in OMV-induced other TLR signaling. Altogether, Cav-1 is a key regulator in OMV-induced multiple TLRs response. This study promotes future research to develop drugs by targeting the specific motif of cav-1 or TLRs against bacterial infection and macrophage-mediated inflammation.